Prevalence of bacterial vaginosis pregnancy - Rojas, José (2015)
OBJECTIVE.- To determine the prevalence of bacterial vaginosis in pregnant women and its relation with other vaginal infections. MATERIAL AND METHODS.- The study was performed at Arzobispo Loayza Hospital from November 1995 through February 1996 in pregnant women who attended their first pre natal control, not using vaginal and/or systemic medication during the last 30 days and without evidence of cervical pathology. The sample was taken in randomized tashion. RESULTS.- We studied 174 patients 16 to 40 year-o1d. Vaginal infection was found in 46,6% patients, including bacterial vaginosis in 27,5%, vaginal candidiasis in 29,3% and trichomoniasis in 5, 1 %, respectively associated infections included bacterial vaginosis with candidiasis in 10,3%. CONCLUSIONS: Vaginal infection is high1y prevalent in our Hospital, similar to findings at other latitudes; we should follow these patients to determine complications.